Digital Advertisement and Its Impact of Online Consumers with Special Reference to Sivakasi Corporation (Journal of Informatics Education and Research, 2024)
The present study made a powerful effort to study the DIGITAL ADVERTISEMENT AND ITS IMPACT OF ONLINE CONSUMERS WITH SPECIAL REFERENCE TO SIVAKASI CORPORATION. Thus, study result shows that especially for digital advertising and its effects on online consumers. According to the study's findings, online shoppers place greater value on internal factor tools, status, development, and satisfaction as compared to brick-and-mortar retailers. Digital advertising has revolutionized how businesses engage with online customers by influencing their purchasing patterns, perceptions of brands, and general online conduct. The elements that consumers take into account while purchasing a product have also been highlighted by this study. Online shoppers may make decisions and shop more conveniently since they have instant access to product information, reviews, and direct links to buy. The sheer volume of digital commercials has resulted in a phenomenon known as "advertisement fatigue," where consumers become overwhelmed or annoyed, leading to ad blockers or ignoring advertisements altogether. On the whole every factor, which are taken into account, influences the purchasing decision of the respondents some extend in digital advertisement.